Participatory on-farm conservation tillage trial in the Ethiopian highland Vertisols: The impact of potassium application on crop yields - Astatke, A.; Mamo, T.; Peden, Donald G.; Diedhiou, M. (Cambridge University Press, 2004)
The two years on-farm tillage research during the 1999 and 2000 cropping seasons in Ethiopian highland Vertisol area demonstrated the importance of adapting cultural practices into participatory trials. The minimum tillage package could be an effective intervention for soil conservation due to the early-vegetative cover of the soil. Based on farmers’ application of ash on Vertisols at Chefe Donsa, the incorporation of 50 kg ha-1 of potassium sulphate (K2SO4) in the on-farm trial significantly increased grain and straw yields of wheat. The nitrogen levels in the grain and straw of wheat on plots given K2SO4 were higher than those without. The nitrogen level for both wheat grain and straw was even higher when grown on plots previously growing legumes that received K2SO4. This showed that the availability of extra potassium in these soils improved the extraction of nitrogen by the wheat crop, thus improving the grain yield. The findings indicate the need to reassess the traditionally-practised system of not applying potassium fertilizer to Ethiopian soils.